L’enseignement de l’attaque au volleyball en classe de Terminale : cas des collèges du Zou - ATOUN, E. Carlos; AGBODJOGBE, D. BASILE; ATTIKLEME, KOSSIVI; Kpazaï, Georges; Ahodonou, Cyriaque (My University, 2018)
In the setting of this survey we fixed ourselves like objective to show three (03) teachers of the EPS the didactic transposition operated at the time of the attack of the volleyball in class of terminal and to compare these didactic transpositions in order to clear gaps between the taught contents and those foreseen like being to teach. To reach this objective we made recourse to certain key concepts of the theory of the antropology of the didactic of Chevallard (1992). The essential results descended of our investigation revealed that the observed teachers had put in work varied forms of attack. This diversity of convenient teaching observe could be bound to reports personal and institutional of these teachers to the object to Know. In the same way to their personal experience. However, gaps exist and acted as trampoline to remedy difficulties of pupils at the time of setting of teaching/ learning and encourage and/ reinforce their level of motor cleverness acquirement. These positive gaps give account of the personal report to the knowledge of teachers as well of their personal and professional experience
Keywords: didactic; transposition; report to the knowledge; attack; volleyball